Pembuatan Aplikasi Dashboard sebagai Alat Monitoring Transaksi Bisnis berbasis Mobile pada Fitur Depayment dari Aplikasi Kios Deliv - Muhammad Lazuardi Adinegara; Buce Trias Hanggara; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT. Deliv Technology Indoraya uses metabase.com for monitoring business transaction data on the Deliv Kios Application. But many of the internal company, especially the directors, are not familiar with the user interface and how to access metabase.com. When they want to monitor data, internal parties always ask the engineer/admin where it will burden their work and the information will not be realtime. Because all business transaction data of PT.Deliv Tehnologi is in the metabase.com so that only directors, engineers, and admins are given access so that access permissions are not evenly distributed in each division of the company. Based on these problems, an Android-based Deliv Kios Dashboard Application is needed in order to assist internal companies in monitoring business transactions that are easy to use and in accordance with the organizational structure and user functionality. System development using the waterfall method, resulting in needs analysis, design, implementation, and testing of the system. All system development data information is based on Key Performance Indicators that have been determined in the needs analysis. The system implementation uses Laravel as the web service framework, and Kotlin on the Android implementation. The results of the implementation of the system are then tested using validation testing, mobile compatibility testing, and usability testing methods. The results of the test show that the system runs according to functional requirements and is able to assist internal companies in monitoring business transactions according to user functionality.